Freaks on the Fells - Ballantyne, R. M. (Saga Egmont, 2022)
Successful London merchant Mr John Sudberry has decided to take his family and three of his servants away on a holiday to the Scottish Highlands. Plenty of beautiful walks, rowing and fishing trips, and picnics in the stunning scenery follow. Their holiday bliss is interrupted however when the family come across an elderly lady called Moggy, who seems to take a special interest in Sudberry's five-year old son Jacky. When Moggy’s secretive background returns to haunt her, the Sudberry family find themselves caught up in the mystery.